Experimental study of the influence of the shear strength of panel zones on the mechanical properties of steel frame structures. (October 2022) - Sui, Weining; Dong, Zheng; Zhang, Xinlong; Wang, Zhanfei
Abstract: The seismic behavior of the steel frame joints can directly affect the response of the structure under earthquake excitation. Steel frame structure systems with a scale ratio of 1:2 were tested under a constant axial force and a low-cycle horizontal reciprocating load. A parametric study was conducted to assess the interaction between the shear capacity of panel zones and the mechanical properties of the steel frame. As a result, although weakening the shear resistance of the panel zones also weakens the strength of the steel frame, the structure has better ductility and energy dissipation capacity. Therefore, a reasonable design of the panel zones is more conducive to improving the seismic performance of the structure. With the decrease in the aspect ratio of the panel zones, though the ultimate bearing capacity of the structure decreases and unfavorable column bending failure mode is observed, the ductility of the panel zones and the energy dissipation increase; reducing the thickness of the panel zones has little influence on ultimate bearing capacity of the frame, however, as the ductility increases, the energy dissipation capacity also increases. The experimental and numerical results for the skeleton curve, stiffness, yield load-bearing capacity, ultimate load-bearing capacity, and stress distribution are similar. The mechanisms of generation of plastic hinges and the final failure mode of steel frame are studied using finite element analysis methods.